Pengaruh Likuiditas, Struktur Aktiva, dan Profitabilitas Terhadap Struktur Modal pada Perusahaan Subsektor Property dan Real Estate yang Terdaftar di Bursa Efek Indonesia (BEI) - Andhika Yusuf Aripranadja; Sarjono Sahar (UNIVERSITAS KALBIS, 2022)
This study aims to determine the effect of liquidity, asset structure, and profitability on capital structure in property and real estate subsector companies listed on the Indonesia Stock Exchange. In this study the sample used is the Property and Real Estate subsector companies listed on the Indonesia Stock Exchange in the period 2015 - 2018 with a sample of 25 companies with 100 observational data. This research uses secondary data in the form of published financial statements. The analysis used in this study is multiple linear regression and the research method used in this study is the purposive sampling method. The results of this study indicate that liquidity has a significant positive effect on capital structure, asset structure has a significant positive effect on capital structure, and profitability has a significant negative effect on capital structure. Simultaneous test results show that liquidity, asset structure, and profitability have a significant positive effect on capital structure.